Autecological characteristics of Centaurea hermannii F. Herm an endemic species from Turkey - (:unkn) unknown (National Centre for Agrarian Sciences, 2014)
This study was performed on Centaurea hermannii F. Herm to acquire information about some characteristics (bioclimatic, edaphic, topographic, biotic etc.) of its habitat and distribution in Istanbul-Turkey. Plant and soil samples were collected between Subaşı and Akalan Villages, in Catalca District of Istanbul. Soil texture, structure and other physical and chemical measurements such as pH, electrical conductivity (EC), saturation, salinity, organic matter, CaCO3 content were determined by using various analyses. The result showed that the soils where plants grow on consist of 34% sand, 34% silt and 32% clay. In the plants, the average contents of some elements (%) were measured as 1.05, 1.05, 2.93 for N, 0.015, 0.02 and 0.034 for P, 0.026, 0.025 and 0.029 for Na, 1.46, 2.58 and 1.90 for K, 1.70, 0.48 and 1.70% for Ca in roots, stems and leaves, respectively. The values above were compared with the values of other Centaurea species in different regions of Turkey. © 2014, National Centre for Agrarian Sciences. All rights reserved.
Keywords: Asteraceae; Mineral nutrition; Plant-soil interactions